The Correlation between Reading Habits and Reading Comprehension of the Eleventh Grade Students at SMAS Darul Falah Aikmel - Maisarah, Khairinka Nurani; Zamzam, Ahmad; Thohir, Lalu (Journal of Authentic Research, 2026)
This study aims to determine whether there is a significant correlation between reading habits and reading comprehension in eleventh-grade students at SMAS Darul Falah Aikmel. This ex post facto study with a quantitative correlational design used two data collection instruments, namely a reading habits questionnaire consisting of 45 items and a multiple-choice reading comprehension test consisting of 20 questions based on narrative texts. The study population was all 63 eleventh-grade students, so a total sampling technique was used. Data were analyzed using Pearson Product-Moment correlation with the help of SPSS 25. The results showed a correlation coefficient (*r*) of .447 and a significance value (*p*) of .000 (< .05). The value of *r* = .447 is included in the category of moderate positive correlation. Thus, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. In conclusion, there is a significant correlation between reading habits and reading comprehension in eleventh-grade students at SMAS Darul Falah Aikmel. This finding indicates that students with better reading habits tend to have better reading comprehension as well. The purpose of this study was to determine whether reading habits and reading comprehension among the eleventh grade students at SMAS Darul Falah Aikmel were significantly correlated. This ex post facto study with quantitative correlational design used two instruments in gathering the data; questionnaire for gathering students’ reading habits and multiple-choice test for assessing students’ reading comprehension. The population was the eleventh grade students at SMAS Darul Falah Aikmel and the sample consisted of 63 students by using population study. Using the SPSS 25 program, the Pearson Product-Moment Correlation was used to measure the data. A positive and significant correlation was indicated by the result of coefficient (r = .447) and the significance value (p < .05). It meant that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. As a result, there was a significant correlation between reading habits and reading comprehension of the eleventh grade students at SMAS Darul Falah Aikmel.